Coordination in some of the basic individual sports: a systematic review - Daniel Stanković; Fatma Neşe Şahin; Emilija Petković; Ana Stanković; Stefan Mijalković (Turkish Journal of Kinesiology, 2023)
The aim of this study was to conduct a systematic review of research that investigates coordination abilities in basic individual sports, such as athletics, gymnastics, climbing, and swimming. The relevant sports that have a process of identifying very young talents are precisely these basic individual sports. The following electronic databases were used: Web of Science and PubMed. A total of 16 studies met the criteria for participation in this study. Since only a few studies have been done on this topic, this review included studies for the last 30 years. The sample of respondents in the included studies consisted of both males and females, and the total number was 642. The study findings indicate that coordination is a crucial motor ability with a significant impact on athletic success in youth. The level of coordination abilities increases with sports experience, so the development of coordination should be one of the priorities in the training process of gymnasts, athletes, sports climbers and swimmers in younger sportsman ages.